Analisi daya saing ekspor nenas segar indonesia - . Suprehatin (Jurnal Ilmu Pertanian Indonesia, 2006)
Pineapple is one of the potential export commodities in Indonesia. The objective of this study is to analyze the competitiveness of pineapple export of Indonesia based on its market share and to examine factors affecting it. The time series and cross section data are estimated by panel data regression. The results show that the competitiveness of Indonesia is lower than others main producers and exporters with the trend of market share is decline. The results also show that export quantly, Gross Domestic Product (GDP) per capita and production quantity are important factors affecting the competitiveness of pineapple export of Indonesia. The results indicate that the export and prodution quantity are positive to market sahre, whereas GDP per capita is negative.